PROBLEMS OF ADEQUATELY CONVEYING IRONY IN TRANSLATION FROM ENGLISH INTO UZBEK - AbduqodirovaMadinaAbduqayumqizi (Western European Studies, 2025)
This study explores the challenges of adequately conveying irony in the process of translating literary texts from English into Uzbek. Irony, as a nuanced and culturally dependent stylistic device, often relies on subtle linguistic cues, shared cultural knowledge, and context-specific humor. These features can become lost or distorted in translation, especially when moving between languages with differing literary traditions and communicative norms. The research examines selected English literary works containing various forms of irony— verbal, situational, and dramatic—and analyzes how translators have rendered these elements in Uzbek. Particular attention is paid to cultural context, metaphorical expression, and the translator’s interpretive choices. The findings highlight frequent cases of semantic shift, tone loss, or over-literal rendering, which can alter the author’s original intent. The study concludes that effective translation of irony requires not only linguistic skill but also deep cultural awareness and creative adaptation strategies.
Keywords: Irony as a rhetorical; cultural construct; literary translation theory